The transfer of symbols and meanings - Milićević Bradač, Marina (Documenta Praehistorica, 2005)
Sir Arthur Evans first used the term "horns of consecration" in 1901. Since then thez have been interpreted in various wazs as Moon idols (Mondidole), boat models, pot stands, loom stands, spit supports, and fire supports. Most, however, can be seen as abstracted bull's horns. Abstraction should have takenplace in Anatolia or northern Mesopotamia, and "horns of consecration" spread verz earlz, appearing, as alreadz defined szmbols in various cultural settings. The question is whether thez stood for the same set of ideas wherever thez appeared, or if meaning varied from one cultural setting to another.
Keywords: arheološke najdbe; neolitik; simboli; symbol; rogovje; Anatolija; Crete; Kreta; Mezopotamija